2005
DOI: 10.1007/s00417-005-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial postoperative endophthalmitis: a 14-year review

Abstract: The overall incidence of endophthalmitis after intraocular surgery was 0.19%. The results of this 14-year review from a local medical center may serve as a source of comparison for other centers and future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
4
34
1
Order By: Relevance
“…Previous reports of ophthalmic infection after corneal transplantation indicate that the risk of donor-to-host microbic transmission is 12-22 times greater when there is a positive donor rim culture [4,7,8]. In addition, if an eye becomes infected after transplantation, most patients will either lose part of their vision or become completely blind [1,2,9]. Therefore, if endophthalmitis occurs after transplantation, the patients need to be treated as soon as possible for the specific microorganism that is responsible for the microbial contamination.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous reports of ophthalmic infection after corneal transplantation indicate that the risk of donor-to-host microbic transmission is 12-22 times greater when there is a positive donor rim culture [4,7,8]. In addition, if an eye becomes infected after transplantation, most patients will either lose part of their vision or become completely blind [1,2,9]. Therefore, if endophthalmitis occurs after transplantation, the patients need to be treated as soon as possible for the specific microorganism that is responsible for the microbial contamination.…”
Section: Introductionmentioning
confidence: 97%
“…Endophthalmitis after penetrating keratoplasty (PK) is an uncommon but serious complication of corneal transplants, occurring in 0.14-0.45% of transplant patients [1][2][3][4][5]. However, donor-to-host transmission of bacteria and fungi is a well-recognized event that can lead to endophthalmitis [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Pei-Chang et al 32 also reported that S. epidermidis was the most frequent organism causing postoperative endophthalmitis. Furthermore, Zhu et al reported that S. epidermidis was the most common isolated organism in culture-positive post-operative endophthalmitis cases.…”
Section: Discussionmentioning
confidence: 95%
“…32 Furthermore, a retrospective study in China recorded a culture-positive rate of 44.2%. 38 Additionally, the current study detected positive cultures in 37% of patients with posttraumatic endophthalmitis, which is lower than other reports such as in Saudi Arabia (63.2%).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Post-cataract endophthalmitis (POE) incidence ranges from 0.04% to 0.13% with differences in regional microbiological spectrum. [9][10][11][12][13][14][15][16] The European Society for Cataract and Refractive Surgery (ESCRS) has recently updated its recommendations for prevention and management of post-cataract endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%